Описание личинок трех видов жуков рода Aphodius (Coleoptera, Scarabaeidae). Сообщение 2 - Мартынов, В.В. (Вестник зоологии, 1999)
Впервые описаны и проиллюстрированы основные морфологические структуры личинок 3-го возраста Aphodius (Bodilus) hydrochoerius F. and Aphodius (Aconthobodilus) immundus Creutzer, личинок 1-го, 2-го и 3-го возраста Aphodius (Bodilus) Iugens Creutzer: структура и хстом головной капсулы, челюстные придатки, вооружение анального стсрнита. Описаны внешняя морфология яиц, особенности яйцекладки и окукливания. Указана изменчивость такого важного систематического признака как количество и размещение центральных лобных ямок. Certain morphological structures of the third-instar larvae of Aphodius (Bodilus) hydrochoerius F. and Aphodius (Aconthobodilus) immundus Creutzer, the 1st instar, the 2nd and the 3rd instar of Aphodius (Bodilus) Iugens Creutzer are described and illustrated for the first time: the structure and chetom of the head capsule, mouth appendages and the anal sternitc armour. External morphology of eggs, peculiarities of egg-laying and pupation are given. The variability of such an important systematic character as the quantity and arrangement of central frontal pits is pointed out.